Determining model configuration for thermal simulation of urban mosque façade design - Abdul Majid, Noor Hanita; Abdullah, Fauziah Hanum; Denan, Zuraini (Malaysian Institute of Planners, 2018)
Urban mosque (UM) façade design, besides its aesthetical role, is a passive architectural design strategy in handling how much heat penetrates into the internal spaces. In determining the model configuration for thermal simulation of urban mosque façade, the orientation and massing of the UM is tested. The orientation of UM relates to the qiblat direction and sun exposure. On the other hand, the massing is defined by the volume of the UM. This research investigates the effects of form layout and volume on thermal performance of the interior environment. A model with no openings on north-westward façade (NWF) and south-eastward façade (SEF) is simulated for a baseline scenario for comparison purposes. Autodesk Ecotect Analysis 2011 is a computer-based simulation tool used in this research to measure the thermal analysis in the UM model. The results indicate the performance of different types of forms, layouts and volumes. By the end of this study, the configuration of the base model is determined according to the results of the orientation and volume variations.